Analisa Faktor-Faktor Yang Berhubungan Dengan Kelengkapan Pengisian Resume Medis Pasien Ruang Rawat Inap dI Rumah Sakit Umum Kabupaten Tangerang - Fitri Zuri Chastuti; Lily Widjaya; Mayang Anggraini (Indonesian of Health Information Management Journal (INOHIM), 2014)
Abstract The advancement of science and technology should be followed by an increase in the quality of services because must face with medicine, of conduct the quality of medical rollin should be the responsibility of health workers, the doctor must provide services in accordance with law medicine no.29 / 2004 ps. 46.To support the quality of service, required the availability of data that is stuffed complete, accurately, timely and can be accounted for avers. Research is aimed for any identifying characteristic doctor and completeness resumes medical and analyzes relations characteristic physician in completeness resumes medical inpatient in RSUD Tangerang. This research use approach survey descriptive analytic, by design cross sectional. Population in this research is all resumes medical inpatient for 1 year rsu in tangerang which totaled 30779 and extracted samples about 106 resumes medical singled out proportional random sampling.Analysis of data using analysis univariat and analysis bivariat chi-square. The result showed resumes medical complete 67 ( 63.2 % ).The result analysis test statistics obtained that side variables age p value = 0.175 so that there was no correlation meaningful between completeness with age. Of variable species of expertise p value = 0.000 so there meaningful relations between completeness with a kind of skills. Of variable working time p value = 0.001 so there meaningful relations between completeness with the work. Of variable status employees p value = 0.013 so there meaningful relations between completeness with the status of employees. Of four independent components only life have no connection to completeness.While the other variables (type expertise working time, status employees) of a connection with completeness.Suggested to familiarize back procedures charging resumes well and right and to always inscribe workup patients immediately recall resumes medical having value to that can be worn by various parties. Keywords: medical, records, resumeAbstrakKemajuan Iptek harus diikuti dengan peningkatan mutu pelayanan karena harus berhadapan dengan etik kedokteran, mutu rekam medis harus menjadi tanggung jawab tenaga kesehatan, dokter harus memberikan pelayanan sesuai dengan UU Kedokteran No.29 th 2004 psl 46. Guna menunjang mutu pelayanan, diperlukan ketersediaan data yang diisi lengkap, secara akurat, tepat waktu serta dapat dipertanggung jawabkan kelengkapannya. Penelitian ini bertujuan untuk mengidentifikasi karateristik dokter dan kelengkapan resume medis serta menganalisa hubungan karateristik dokter dengan kelengkapan resume medis Rawai Inap di RSU Kabupaten Tangerang. Metode Penelitian ini menggunakan pendekatan survei deskriptif analitik, dengan desain cross sectional. Populasi dalam penelitian ini adalah seluruh resume medis rawat inap selama 1 tahun di RSU Kabupaten Tangerang yang berjumlah 30779 dan diambil sampel sebanyak 106 resume medis yang dipilih secara propotional random sampling. Analisis data menggunakan analisis univariat dan analisis bivariat chi-square. Resume medis yang lengkap sebesar 67 (63.2%). Hasil analisis uji statistik didapat bahwa variable umur P Value= 0.175 (p>0.05) sehingga tidak terdapat hubungan yang bermakna antara kelengkapan dengan umur. Variable jenis keahlian P Value= 0.000 (p<0.05) sehingga terdapat hubungan yang bermakna antara kelengkapan dengan jenis keahlian. Variable Masa Kerja P Value= 0.001 (p>0.05) sehingga terdapat hubungan yang bermakna antara kelengkapan dengan masa kerja. Variable status kepegawaian P Value= 0.013 (p>0.05) sehingga terdapat hubungan yang bermakna antara kelengkapan dengan status kepegawaian. Dari empat komponen independen hanya umur yang tidak ada hubunganya dengan kelengkapan. Sedangkan variable lainnya (jenis keahlian, masa kerja, status kepegawaian) ada hubungan dengan kelengkapan. Disarankan agar mensosialisasikan kembali tata cara pengisian resume dengan baik dan benar dan untuk selalu menuliskan hasil pemeriksaan pasien dengan segera mengingat resume medis memiliki nilai guna yang dapat dipakai oleh berbagai pihakKata kunci: medis, rekam, resume